Certification of interpreters: an overview and best practices internationally - Petrocheilou, Maria (International Journal of Language, Translation and Intercultural Communication, 2025)
Over the past few years, the issue of certification has emerged as an issue of paramount importance for all professions, including interpreting. While certification is a voluntary procedure, there is confusion about the use of terminology around the world: in Texas reference is made to licensed court interpreters, while the central website of US Courts of Justice speaks of “certified interpreters”, although in both cases interpreters voluntarily undergo exams at the court to be registered as interpreters. In the case of court interpreters, reference is made to “court certified, registered και enrolled interpreters”, without any difference in the meaning of each one of them, while in the United Kingdom the term “chartered linguist” is widespread. Since its foundation the European Union has been organizing “accreditation tests” for the freelance interpreters it occasionally recruits to cover its interpreting needs, while national interpreters’ associations have started issuing quality certification for their members over the past few years based on their national legislation. Interesting examples of certification are presented (Assointerpreti, AIIC Italia, Universitas Austria) as they could be a source of inspiration for other countries, since they are based on the compliance with certain legal requirements and interestingly do not entail any additional bureaucratic burden or cost for the public sector. In the field of Registers of Public Service Interpreters, Norway and the UK lead by example within Europe. Norway has had a Register of Public Service Interpreters since 2005, while the National Register of Public Service Interpreters (NRPSI) provides a database of the UK’s registered interpreters. Last but not least, reference is made to ISO certification and in particular to ISO 13611 on Community Interpreting Services.